2019
DOI: 10.32598/ijpcp.25.3.328
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Object Relations and the Severity of Depression Symptoms: The Mediating Role of Self-Compassion

Abstract: Objectives The current research investigated the mediating role of self-compassion in the connection between object relations and the severity of depression symptoms. Methods This was a descriptive and correlational study. The study sample consisted of 245 male and female students residing in the dormitories of Iran University of Medical Sciences in the academic year of 2017-18. They were selected based on the two-step cluster sampling method. The subjects answered the Bell Object Relations and Reality Testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Psychologically, this decade is associated with the development of social relationships and defects in the pattern of object relations and emotional regulation in healthy individuals at this point can be manifested in the form of disorders in the quality of life and psychological well-being. A study on healthy individuals between the ages of 18 and 41 confirmed the association between object relationships and the severity of depressive symptoms ( 17 ).…”
mentioning
confidence: 80%
“…Psychologically, this decade is associated with the development of social relationships and defects in the pattern of object relations and emotional regulation in healthy individuals at this point can be manifested in the form of disorders in the quality of life and psychological well-being. A study on healthy individuals between the ages of 18 and 41 confirmed the association between object relationships and the severity of depressive symptoms ( 17 ).…”
mentioning
confidence: 80%